Предмет: Математика,
автор: 20LeNa07
(x-6)(x+12)=0 розв’язання
Ответы
Автор ответа:
0
Ответ:
Пошаговое объяснение:
(X-6)(x+12)=0
(X-6)×(x+12)=0
X-6=0
X+12=0
X=6
X=-12
X1=-12; X2=6
Автор ответа:
0
(x-6)(x+12)=0
x-6=0 x+12=0
x=6 x=-12
Відповідь: x1=-12 x2=6
x-6=0 x+12=0
x=6 x=-12
Відповідь: x1=-12 x2=6
Похожие вопросы
Предмет: Физика,
автор: julialove7
Предмет: Математика,
автор: кавказ001
Предмет: Математика,
автор: умник1234567890
Предмет: Биология,
автор: Ринат626
Предмет: Математика,
автор: Ofilippova99